YKL-40 - A NEW DIAGNOSTIC BIOMARCER FOR BENIGN BREAST DISEASES AND BREAST CANCER - Vanya Uzunova; G. Paskalev; Maria Kazakova; E. Poryazova; K. Murdjev; A. Uchikov; A. Iankulov; Victoria Sarafian; D. Manolova; A. Paskaleva; B. Hadjiev; J. Grudeva-Popova (Peytchinski Publishing, 2010)
Benign breast diseases encompass a wide spectrum of lesions, which raise a lot of questions about their classification, diagnosis, prognosis and surgical treatment. The aim of this study is to measure the serum level of YKL-40 in cases of different groups of benign breast diseases, to compare it to the level of healthy women as well as to those with breast cancer and to examine its tissue expression after surgical treatment. We use it as a diagnostic marker and as a criterion for differential diagnosis.Forty nine (49) patients with benign breast diseases and twenty (20) patients with breast cancer were examined. All of them had their serum level of YKL-40 measured preoperatively and its tissue expression examined immunohystochemically after the surgical intervention. There were significant differences in both concentration and tissue expression of this marker in patients with different groups of benign breast diseases and breast cancer. YKL-40 can be an important biomarker in the diagnosis and differential diagnosis of breast diseases.